Catalogue of the Arabic manuscripts in the Library of the Hungarian Academy of Sciences - Dévényi, Kinga.; Abdul-Fattah, Munif.; Fiedler, Katalin, 1984- (Islamic Manuscripts and Books, 2016)
The Library of the Hungarian Academy of Sciences ‒ established in 1826 ‒ houses many small and still hidden collections. One of these, the most comprehensive Hungarian collection of Arabic manuscripts, is brought to light by the present catalogue. These codices are described for the first time in a detailed and systematic way. A substantial part of the manuscripts is either dated to or preserved from the 150 year period of Ottoman occupation in Hungary. The highlights of the collection are from the Mamluk era, and the manuscripts as a whole present a clear picture of the curriculum of Islamic education. The descriptions also give an overview of the many additional Turkish and Persian texts thereby adding to our knowledge about the history of these volumes.